Chemokines Associated with Pathologic Responses to Orthopedic Implant Debris - Hallab, Nadim J.; Jacobs, Joshua J. (Frontiers in Endocrinology, 2017)
Despite the success in returning people to health saving mobility and high quality of life, the over 1 million total joint replacements implanted in the US each year are expected to eventually fail after approximately 15-25 years of use, due to slow progressive subtle inflammation to implant debris compromising the bone implant interface. This local inflammatory pseudo disease state is primarily caused by implant debris interaction with innate immune cells, i.e. macrophages. This implant debris can also activate an adaptive immune reaction giving rise to the concept of implant related metal sensitivity. However, a consensus of studies agree the dominant form of this response is due to innate reactivity by macrophages to implant debris danger signaling (DAMP) eliciting cytokine-based and chemokine inflammatory responses. This review covers implant debris induced release of the cytokines and chemokines due to activation of the innate (and the adaptive) immune system and how this leads to subsequent implant failure through loosening and osteolysis, i.e what is known of central chemokines (e.g. IL-8, MCP-1, MIP-1, CCL9, CCL10, CCL17, CCL22) associated with implant-debris reactivity as related to the innate immune system activation/cytokine expression, e.g. danger signaling (e.g. IL-1beta, IL-18, IL-33 etc), toll-like receptor activation (e.g. IL-6, TNF-alpha etc), bone catabolism (e.g. TRAP5b) and hypoxia responses (Hif1-alpha). More study is needed however, to fully understand these interactions to effectively counter cytokine and chemokine based orthopedic implant related inflammation.